The Existence of Islamic Boarding School Education in the Spiritual and Socio-Cultural Development of Society - Lubis, Mira Yanti; Ritonga, Mahyudin (STIT Ahlussunnah Bukittinggi, 2025)
Pesantren education is not only a center for religious learning, but also a pillar for character building, tradition preservation, and local cultural value development through intellectual, spiritual, and social integration. This literature review analyzes the existence of pesantren in a socio-cultural context, demonstrating its flexibility in facing globalization while maintaining Indonesia's Islamic identity. Pesantren contribute to local economic empowerment through practical skills, ensuring the spiritual and cultural sustainability of the community. The existence of pesantren is supported by their ability to preserve Islamic scholarly traditions, adapt to changing times, and actively contribute to socio-cultural life.